Science Knows the Answers for Fishing but Politicians Are Acting the Wrong Way - João P Barreiros (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2016)
Marine Protected Areas (MPA's) in the World are small and, more often than not, badly managed. In fact, the total area of MPA's is not bigger than that of South Africa. However, if we remove MPA's where some kind of traditional fishing is allowed that total is about the size of Holland - which means next to zero [1].                                                                               Fishing policies in many countries around the World, and this includes many of the so-called 1st world countries are 'limited' by short to mid-term decisions in face of short electoral calendars [2]. This means that decisions on bans, moratoria and MPA's are simply dominated by political calendars and not by sound long-term scientific studies many of which have proven to be sound and wise for a sustainable use of marine (and also other aquatic) resources.